Simple amplifier configuration algorithm for dynamic C + L-band systems in the presence of stimulated Raman scattering - Song, Yuchen; Fan, Qirui; Lu, Chao; Wang, Danshi; Lau, Alan Pak Tao (Optics letters, 2022)
We propose a simple two-step amplifier configuration algorithm based on signal power across different channels to improve the generalized signal-to-noise ratio (GSNR) performance of dynamic C + L-band links in the presence of amplifier spontaneous emission (ASE) noise, Kerr nonlinearity, and stimulated Raman scattering (SRS) using erbium-doped fiber amplifiers (EDFA). In step 1, ASE noise and Kerr nonlinearity are taken into account to derive sub-optimal signal power profiles at the beginning of each span using the local optimization global optimization (LOGO) strategy. The effect of SRS is compensated through amplifier gain pre-tilt in step 2. Simulations for links with homogeneous/heterogeneous spans, static full-channel loading, and dynamic loading due to gradual channel additions for C + L-band upgrades show that the proposed algorithm can achieve similar GSNR performance, but requires much less execution time, compared to other iterative methods that target for improving the GSNR across the C + L band, thus making it a fast and efficient GSNR management strategy for future dynamic C + L-band networks.We propose a simple two-step amplifier configuration algorithm based on signal power across different channels to improve the generalized signal-to-noise ratio (GSNR) performance of dynamic C + L-band links in the presence of amplifier spontaneous emission (ASE) noise, Kerr nonlinearity, and stimulated Raman scattering (SRS) using erbium-doped fiber amplifiers (EDFA). In step 1, ASE noise and Kerr nonlinearity are taken into account to derive sub-optimal signal power profiles at the beginning of each span using the local optimization global optimization (LOGO) strategy. The effect of SRS is compensated through amplifier gain pre-tilt in step 2. Simulations for links with homogeneous/heterogeneous spans, static full-channel loading, and dynamic loading due to gradual channel additions for C + L-band upgrades show that the proposed algorithm can achieve similar GSNR performance, but requires much less execution time, compared to other iterative methods that target for improving the GSNR across the C + L band, thus making it a fast and efficient GSNR management strategy for future dynamic C + L-band networks.